2021
DOI: 10.1080/08941939.2021.1933274
|View full text |Cite
|
Sign up to set email alerts
|

Impact of Three Methods of Ischemic Preconditioning on Ischemia-Reperfusion Injury in a Pig Model of Liver Transplantation

Abstract: Background. Ischemic preconditioning (IPC), either direct (DIPC) or remote (RIPC), is a procedure aimed at reducing the harmful effects of ischemia-reperfusion injury. Aims. To assess the local and systemic effects of DIPC, RIPC, and both combined, in the pig liver transplant model. Methods. Twenty-four pigs underwent orthotopic liver transplantation and were divided into 4 groups according to the procedures applied: direct donor preconditioning; indirect preconditioning at the recipient and a group with direc… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
3
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 42 publications
(26 reference statements)
1
3
0
Order By: Relevance
“…Also, we observed that the differences among the groups are more notable at the gene expression level, secondarily at the histological level, and less evident at the histomorphometric level. This might occur because gene expression changes are more precocious and precede morphological changes at the tissue level, as we found in a previous investigation from our group 16 .…”
Section: Discussionsupporting
confidence: 56%
See 1 more Smart Citation
“…Also, we observed that the differences among the groups are more notable at the gene expression level, secondarily at the histological level, and less evident at the histomorphometric level. This might occur because gene expression changes are more precocious and precede morphological changes at the tissue level, as we found in a previous investigation from our group 16 .…”
Section: Discussionsupporting
confidence: 56%
“…As an initial consideration, it may emphasize that the different modalities of IPC are impractical procedures that may further increase the already high complexity of transplantation surgery. This conclusion was based on a sequence of experimental investigations performed in a pig model of liver transplantation in which it was demonstrated that direct, remote ischemic preconditioning or a combination of both, produce beneficial effects only at the molecular level, without any biochemical or histological advantages 15,16 . These studies led to the conclusion that the benefits' procedures are not consistent and may not be applied to liver transplantation in humans.…”
Section: Discussionmentioning
confidence: 99%
“…For example, RIC may promote the production of some active substances (opioids, adenosine, bradykinin and stromal cell-derived factor-1, etc.) and accelerate their entry into the blood, thus activating neural networks and acting on the target organs of the human body ( 38 , 39 ). In addition, RIC may also activate antiapoptotic ( 40 ), antioedema ( 41 ), and anti-inflammatory signalling pathways ( 42 ), improve microvascular endothelial function ( 43 ), and affect the transcription of related genes and mitochondrial respiratory function ( 44 , 45 ), thereby reducing the impact of I/R injury.…”
Section: Discussionmentioning
confidence: 99%
“…The underlying mechanisms of protection remain poorly understood but involve neural, humoral and systemic pathways and include a downregulation of oxidative stress and upregulation of protective pathways within the transplant organ [19]. Whilst experimental animal models have provided promising results, there has been limited translation into clinical practice [20][21][22][23][24].…”
Section: Introductionmentioning
confidence: 99%